Effect of γ-ray irradiation on Dielectric and AC conductivity of AN-AMPS Copolymers - A. Narender (International Journal of Scientific Research in Science and Technology, 2025)
To study the Gamma ray irradiation effect on dielectric and AC Conductivity of AN-AMPS copolymers. A systematic measurement of Dielectric constant (ϵ) and loss (tanδ) on powder pressed pellets of AMPS with AN copolymer in Composition 50/50 have been carried out before and after gamma ray irradiation in the frequency range 200Hz to 100kHz and in the temperature range from room temperature to 180OC covering through glass transition temperature (Tg). AC Conductivity(σAC) of the copolymers has evaluated. The effect of gamma ray irradiation on dielectric and AC Conductivity properties of AN-AMPS Copolymers has been investigated. Here we observed the change in the variation of dielectric constant, dielectric loss and AC Conductivity with frequency and temperature before and after γ- ray irradiation. It has been found that the composition of the copolymer influences how radiation impacts conductivity.
Keywords: Dielectric constant; dielectric loss; AC Conductivity; Gamma ray irradiation